2014
DOI: 10.1161/atvbaha.113.302927
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2C8 ω3-Long-Chain Polyunsaturated Fatty Acid Metabolites Increase Mouse Retinal Pathologic Neovascularization—Brief Report

Abstract: Objective Regulation of angiogenesis is critical for many diseases. Specifically, pathological retinal neovascularization, a major cause of blindness, is suppressed with dietary ω3-long-chain polyunsaturated fatty acids (ω3LCPUFAs) through antiangiogenic metabolites of cyclooxygenase and lipoxygenase. Cytochrome P450 epoxygenases (CYP2C8) also metabolize LCPUFAs, producing bioactive epoxides, which are inactivated by soluble epoxide hydrolase (sEH) to transdihydrodiols. The effect of these enzymes and their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 27 publications
3
57
1
Order By: Relevance
“…Although not definitively shown, it was suggested that the CYP2C8 expressed in monocytes/macrophages was upregulated during oxygeninduced retinopathy, whereas the sEH was suppressed to result in an increased retinal epoxide/diol ratio. Interestingly, retinal neovascularization increased when animals were given a v-3 PUFA-rich diet, whereas there was no effect of the diet in animals maintained under normoxic conditions (Shao et al, 2014). Apart from emphasizing the importance that diet has on the balance of lipid mediators generated by the sEH axis, this report underscores the need to carefully screen lipid profiles in different tissues before jumping to conclusions about which of the P450-derived lipid mediators are the most bioactive.…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 81%
See 1 more Smart Citation
“…Although not definitively shown, it was suggested that the CYP2C8 expressed in monocytes/macrophages was upregulated during oxygeninduced retinopathy, whereas the sEH was suppressed to result in an increased retinal epoxide/diol ratio. Interestingly, retinal neovascularization increased when animals were given a v-3 PUFA-rich diet, whereas there was no effect of the diet in animals maintained under normoxic conditions (Shao et al, 2014). Apart from emphasizing the importance that diet has on the balance of lipid mediators generated by the sEH axis, this report underscores the need to carefully screen lipid profiles in different tissues before jumping to conclusions about which of the P450-derived lipid mediators are the most bioactive.…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 81%
“…This may well be the case, especially when considering the reports that link increased EET production or reduced EET metabolism with cancer metastasis (see below). A recent report also links the Tie2-driven overexpression of the human CYP2C8 isoform with retinal pathologic neovascularization in mice (Shao et al, 2014). Although not definitively shown, it was suggested that the CYP2C8 expressed in monocytes/macrophages was upregulated during oxygeninduced retinopathy, whereas the sEH was suppressed to result in an increased retinal epoxide/diol ratio.…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 99%
“…These sums provide an index of the overall CYP450-mediated epoxygenation toward each of the fatty acids ( 6,16 ). We also secondarily assessed each MEFA regioisomer derived from the same PUFA, as well as the epoxide:diol ratio for each MEFA, an index that is inversely correlated with soluble epoxide hydrolase activity and has been suggested to be a proxy for the enzyme activity in vivo ( 17,18 ). We evaluated this ratio in our study because n-3 PUFA supplementation has been shown in animal studies to change soluble epoxide hydrolase expression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is therefore a potential therapeutic target, and the manipulation of its expression or activity (and therefore the epoxide:diol ratio) in animal studies infl uences infl ammation and other physiological parameters (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…[99] In this context, Agbor et al [100] demonstrated the contribution of isoform CYP1A1 tothe metabolism of n3-PUFAs, and the activation of endothelial nitric oxide synthase and consequent increase innitric oxide (NO) bioavailability associated with a diet rich in n3-PUFAs [ Figure 5]. Furthermore, a study by Hoshi et al…”
Section: [98]mentioning
confidence: 99%